Fall-Related Risk Factors among Older Men: A Scoping Review - Temitope Olokunlade; Mark E. Benden; Gang Han; Ledric Sherman; Oluyomi Oloruntoba; Igwesiri Jessa; Author Igbo; Johncross Nwadije; Toriq Mustapha; Adaeze Nwufo; Adetoun Ogunbamowo; Matthew L. Smith (Health Behavior Research, 2024)
Unintentional falls cause significant morbidity and are major contributors to mortality among older adults, but less is known about fall-related risk for older men. This study identified modifiable and nonmodifiable risk factors for incident and recurrent falls among older males ages ≥60 years. We searched Medline (OVID), CINAHL, Ultimate, Cochrane, and Embase, for observational studies showing risk factor association with falls among community-based older adult populations. Two hundred studies were identified and 38 met the inclusion criteria. Sixty risk factors, ranging from behavior to environmental, were reviewed. The main risk factors associated with incident and recurrent falls include pain, age, depression, fear of falling, activity/mobility limitations, sleep disorder/chronic hypoxemia, and multimorbidity. Some risk factors, such as pain and multimorbidity, demonstrated dose-response relationships with recurrent falls. Primary studies are needed to investigate the effects of these risk factors on falling among older adult males, with considerations for racial/ethnicity differences.